Cak Nur: Intelektual Cerdas Indonesia (Studi Biografi) - Ahmad Nabil Amir; Tasnim Abdul Rahman (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2021)
Looking from its surface, the highly superior and exceptional works of Nurcholish Madjid seems to invite his readers to argue and converse with him with absolute freedom without giving bother to any accusations or charges of anarchy. His writings that was full with philosophical arguments was constructed to inspired dialectical discussion and reasoning without ascribing to any established school of thought of the past. With his masterful works, it tries to challenges and draws our consciousness of the real force of intellectualism that was derived from scientific reflection and critical philosophical inquiry. It’s strength was derived from the empirical and historic method and framework in his effort to formulate and comprehend classical Islam and its intellectual tradition in term of its contextual and modern understanding and process.